One Gram of Gold - Frohn Pedersen, Anna; Mkai, Patric Jude; Mwenda, Robert; Msuya, Raphael (Journal of Anthropological Films, 2025)
This film is about gold– a global commodity shaping local livelihoods and landscapes across the world. It is about the people who risk their lives in the narrow underground mines and about their struggles for a better future. It is a participatory project that aims to move beyond an ethnocentric gaze on mining, giving voice to local perspectives and portraying the everyday as it is lived in Nyarugusu, a mining village in the northern part of Tanzania. Raphael Msya and Robert Mwenda, two miners from Nyarugusu, are the reporters, interviewing fellow miners and guiding us through the gold mining landscape, from the humid underground tunnels to the dusty processing sites. They not only show us the risks, challenges and uncertainties that are embedded in mining but also the hopes and dreams it invokes. Their stories highlight the ambiguity of a sector that is degrading landscapes and endangering lives, but at the same time crucial for providing a livelihood.